A Multisensory AI-based Framework for Accessible Navigation of Visually Impaired Users in Virtual Environments: Preliminary Results - Cintra, Luiza M. F.; Oliveira, Elisa A. M.; Barbosa, Gustavo H. W.; Negrão, Matheus D.; G. Neto, Valdemar V.; Sousa, Rafael T.; Paiva, Sofia L. C.; G. Filho, Arlindo R. (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
Virtual reality has the potential to deliver highly immersive experiences, but for individuals with visual impairments, these environments often remain inaccessible and exclusionary. This paper introduces an AI-driven framework that redefines how such users interact with 3D virtual worlds. The system employs Vision-Language Models (VLMs) for real-time semantic scene understanding, translating visual information into auditory cues and haptic feedback. This multisensory approach allows users to perceive spatial layouts, recognize objects, and navigate with greater autonomy. By bridging the gap between visual content and non-visual perception, the framework turns virtual reality into a more inclusive, equitable, and engaging medium.